Multiple photopigments from the Mexican blind cavefish, Astyanax fasciatus: a microspectrophotometric study. - Parry, J; Peirson, S; Wilkens, H; Bowmaker, J (2003)
The cave-dwelling (hypogean) form of the teleost Astyanax fasciatus is blind, having only subdermal eye rudiments, but nevertheless maintains intact opsin genes. Second generation offspring of a cross between these and the normally sighted surface (epigean) form inherit opsin genes from both ancestries. A study of the expressed hypogean opsins of the hybrids, in comparison to the epigean forms, was undertaken by microspectrophotometry. The hybrid population showed considerable variation in the visual pigments of double cones, with evidence for two groups of cells with lambda(max) intermediate to those of the epigean pigments. Possible explanations for these intermediate pigments are discussed, including the hypothesis that they may represent hybrid genes similar to the genes for anomalous cone pigments in humans. Evidence was also found for ultraviolet-sensitive single cones and for an additional MWS pigment.